The development of multi-agent system for biological information retrieval from heterogeneous distributed data and knowledge sources - Mat Yatim, Safie; Othman, Muhamad Razib; Deris, Safaai; Md. Illias, Rosli (Faculty of Computer Science and Information System, 2006)
Distribution, complexity, heterogeneity of resources, software, and hardware are challenges in distributed applications. Intelligent mobile agent is used to handles distributed data, control, expertise, and resources in distributed applications. It is an executing program that is capable of flexible autonomous action, migrates during execution from host to host, reason with uncertain, incomplete, and contradictory information. Belief-Desire-Intention-Joint-Mobile UNITY (BDI-MU) kit is introduced to construct intelligent mobile agent. It is designed using BDI-MU architecture. BDI-MU architecture is an open architecture based on autonomous practical reasoning and social ability through messages. It consists of system package and user-defined package. The system package provides components that can be extended and imported to develop an agent, its server and domain. The user-defined package is a pluggable component which consists of user applications, agents and databases. The BDI-MU agent constructed by BDI-MU kit is composed by intra agent structure and inter agent structure. The intra agent structure provides belief, intention, capability, and goal for reasoning. Autonomy and BDI architecture is used to construct the intra agent structure. The inter agent structure provides functionality for communicating with other individuals, coordinating with agencies, accessing resources, and mobility within the network. Message and Mobile UNITY is used to construct the inter agent structure. Ambients hierarchy and holonic organization framework is integrated to develop a component and organizational based intelligent mobile agent. To ensure a systematic BDI-MU agent based system development process, a BDI-MU methodology and BDI-MU modeling technique are proposed as a modeling language, rules, and practices. The experimental results show that the BDI-MU agent produced by the BDI-MU kit performed efficiently.